The Intermediality of Ukrainian Fantasy - Олійник, Світлана Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article focuses on the relations of literary texts (novel of D. Korniy “Honyhmarnyk”, the short story of M. Sokolyan “Ballad for Crooked Varga” and the novels “The puppeteer”, “The puppet” and “The Puppet-maker" of the series “The Ecumene” by Henri Layon Oldi) with the imaginative structures of other arts. The article studies how the literary text is quoting music, theater, cinema or painting texts. Also this article deals with the ways of contact between linguistic means of expression and artistic means of non-verbal arts. The Intermedial analysis of these texts allows to explore the deeper cultural polylogue of these texts, means and techniques for images generating, and specify the genre of these texts.